Fluxos migratórios no futebol: uma análise geográfica da copa do mundo da FIFA 2018 - Jacob, Felipe Ezequiel [UNESP] (2019)
This paper aims to analyze the impact of migratory flows in football, especially in relation to the colonial connection between European, African and South American countries. The object of study is the 2018 FIFA World Cup, held in Russia, which had a large number of naturalized players, as well as descendants, where the influence of the past is still present, concerning the domination of rich countries over the poor